Assessment of Contamination and Misclassification Biases in a Randomized Controlled Trial of a Social Network Peer Education Intervention to Reduce HIV risk Behaviors Among Drug Users and Risk Partners in Philadelphia, PA and Chiang Mai, Thailand - Simmons N. (Springer New York, 2015)
© 2015 Springer Science+Business Media New York Controlled trials of HIV prevention and care interventions are susceptible to contamination. In a randomized controlled trial of a social network peer education intervention among people who inject drugs and their risk partners in Philadelphia, PA and Chiang Mai, Thailand, we tested a contamination measure based on recall of intervention terms. We assessed the recall of test, negative and positive control terms among intervention and control arm participants and compared the relative odds of recall of test versus negative control terms between study arms. The contamination measures showed good discriminant ability among participants in Chiang Mai. In Philadelphia there was no evidence of contamination and little evidence of diffusion. In Chiang Mai there was strong evidence of diffusion and contamination. Network structure and peer education in Chiang Mai likely led to contamination. Recall of intervention materials can be a useful method to detect contamination in experimental interventions.